Tolerance of Paramysis lacustris and Limnomysis benedeni (Crustacea, Mysida) to sudden salinity changes: implications for ballast water treatment - Zita Rasuolė Gasiūnaitė Asta Audzijonytė; rina Ovčarenko (Oceanologia)
In order to draw implications for ballast water management, wetested the tolerance of two Ponto-Caspian mysid species Paramysislacustris and Limnomysis benedeni to sudden salinitychanges. The naturally stenohaline P. lacustris was more susceptibleto higher salinities; its mortality rate at 19 PSU was 60%,whereas exposure to 23 PSU was 100% lethal. The euryhaline L.benedeni survived in salinities of up to 19 PSU, but experienced100% mortality at 34 PSU. The return of both mysid species tofresh water after the 24 h exposure to higher salinities didnot prevent further mortality. Considering the rather high short-termsalinity tolerance of both species, a salinity of at least 30PSU should be used as an appropriate biocide.